TMCRO: Traffic Management based on Cognitive Radio Optimization (International Journal of Psychosocial Rehabilitation, 2020)
As per ongoing estimations, consistent population development and urbanization will bring an extra stack of 2.9 billion vehicles to street arrangements by 2050. This will surely prompt expanded air contamination concerns, exceptionally blocked streets putting more strain on a previously broken foundation, and may build the danger of accidents on the streets also. Subsequently, to confront these issues, we need not exclusively advance the use of more intelligent and greener methods for transportation, yet in addition to configuration-propelled arrangements that influence the capacities of these methods alongside present-day urban communities' street frameworks to expand their utility. To this end, we propose a unique traffic management based on cognitive radio optimization, named TMCRO, that expects to emulate the standard of cognitive radio innovation utilized in remote systems on street systems. The key thought behind TMCRO is to briefly give normal vehicles access to need (e.g., transport or carpool) paths at whatever point they are underutilized so as to lessen street traffic clog. The presentation assessment consequences of TMCRO utilizing a framework and arbitrary street-organized topologies with fluctuating traffic load have demonstrated its viability.